Optimalisasi Pencegahan Hipertensi di Masyarakat melalui Program CERDIK - Febriani, Kiswah Anggita; Cahya, Ananda Thereza Nugroho Eka; Nujud, Nasywa Huwaidah; Wismiarti, Wahyu Dian; Septianingtyas, Maya Cobalt Angio; Noeraini, I’ien; Rusmiyati, Rusmiyati (Global Health Science Group, 2025)
Hipertensi, yang sering disebut